Motor recruitment to the TIM23 channel’s lateral gate restricts polypeptide release into the inner membrane - Schendzielorz, Alexander Benjamin (Nat Commun, 2018)
The presequence translocase of the mitochondrial inner membrane (TIM23 complex) facilitates anterograde precursor transport into the matrix and lateral release of precursors with stop-transfer signal into the membrane (sorting). Sorting requires precursor exit from the translocation channel into the lipid phase through the lateral gate of the TIM23 complex. How the two transport modes are regulated and balanced against each other is unknown. Here we show that the import motor J-protein Pam18, which is essential for matrix import, controls lateral protein release into the lipid bilayer. Constitutively translocase-associated Pam18 obstructs lateral precursor transport. Concomitantly, Mgr2, implicated in precursor quality control, is displaced from the translocase. We conclude that during motor-dependent matrix protein transport, the transmembrane segment of Pam18 closes the lateral gate to promote anterograde polypeptide movement. This finding explains why a motor-free form of the translocase facilitates the lateral movement of precursors with a stop-transfer signal.